2012
DOI: 10.1016/j.evalprogplan.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Development and piloting of a mother and child intervention to promote resilience in young children of HIV-infected mothers in South Africa

Abstract: This paper describes the process of developing a parallel intervention for HIV-positive mothers and their young children (6-10 years) with a view to strengthening the relationship between them. Strong mother-child relationships can contribute to enhanced psychological resilience in children. The intervention was developed through action research, involving a situation analysis based on focus group discussions; intervention planning, piloting the intervention and a formative evaluation of the intervention. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…[39] The conceptual framework has been described previously [39] and is based on the understanding that the psychological trauma experienced by mothers dealing with HIV,[13-16] and the resulting compromised parenting contributes to children's behavioral difficulties and poor functioning. [8,19-22] Thus the intervention was designed not only to improve the wellbeing of the mother and child but also the interaction between them.…”
Section: Introductionmentioning
confidence: 99%
“…[39] The conceptual framework has been described previously [39] and is based on the understanding that the psychological trauma experienced by mothers dealing with HIV,[13-16] and the resulting compromised parenting contributes to children's behavioral difficulties and poor functioning. [8,19-22] Thus the intervention was designed not only to improve the wellbeing of the mother and child but also the interaction between them.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that there are caregivers who show resilience and work very hard to care for their children. Interventions directed at the mother-child relationship were able to further enhance HIV-positive mothers' capacity to cope beter with their own illness and, as a result, be able to build psychological resilience in their children [58]. It is well demonstrated that resilience has the capacity to afect the long-term trajectory of a child's emotional, cognitive and adaptive functioning.…”
Section: Enhancing Resilience As a Protective Coping Mechanismmentioning
confidence: 99%
“…While evidence suggests that maternal illness is considered a risk for poor outcome in their children, where HIV-positive mothers were given the opportunity to enhance their capacity to deal with their illness and to strengthen parent-child relationship, the outcomes proved to beneit both the mental health of the caregiver and the child [33,39]. A few studies that emerged have started looking at the resilience in young children whose mothers are living with HIV in an atempt to improve developmental and psychosocial outcomes for both the HIV-infected mother and the child [17,33,39,47,58]. In the study with HIV-positive mothers from South Africa, there were also HIV-positive mothers who were able to express their own desires to live positively, for themselves and their children; they were also able to recognise how their own behaviour was afecting their children, and this had a positive impact on their ability to parent and communicate efectively with their children [58].…”
Section: Enhancing Resilience As a Protective Coping Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Such dynamics are exacerbated in settings such as Rwanda where the dual vectors of HIV and AIDS and the legacy of the 1994 Genocide have disrupted many traditional mechanisms of child-rearing with devastating consequences for children and families [13–15]. Despite these challenges, few evidence-based programmes have been developed to promote healthy family functioning and to prevent mental health problems in HIV-affected children in sub-Saharan Africa [16,17]. …”
Section: Introductionmentioning
confidence: 99%